Does Focus of Attention Improve Snatch Lift Kinematics?. Issue 10 (October 2017) - Schutts, Kyle S.; Wu, Will F.W.; Vidal, Anthony D.; Hiegel, Jamie; Becker, James
Abstract : Abstract: Schutts, KS, Wu, WFW, Vidal, AD, Hiegel, J, and Becker, J. Does focus of attention improve snatch lift kinematics? J Strength Cond Res 31(10): 2758–2764, 2017—Recent motor control literature has demonstrated that using verbal instructions to direct a performer's attention externally (i.e., toward the movement outcome) enhances motor skill performance. The purpose of this study was to investigate how an athlete's focus of attention impacts kinematic performance of the snatch. Using a counterbalanced within-participant design, 12 competitively trained athletes (8 male and 4 female athletes) performed 2 instructional blocks of 3 snatch repetitions at 80% of their most recent training 1 repetition maximum. Blocks of internal and external instructions were given to the athlete in a random fashion. Results showed that, when focusing internally, athletes significantly ( p ⩽ 0.05) increased elbow velocity relative to focusing externally, whereas the external instructions significantly increased horizontal barbell velocity, relative to internal instructions. Additionally, an internal focus resulted in significantly larger barbell-cervical-hip angles at maximum height of the barbell compared with an external focus, indicating that the athletes squatted under the barbell too soon. This information adds to the literature suggesting small changes in coaching instructions can impact performance significantly. It is recommended that coaches use instructions that direct an athlete's attention externally, toward the movement outcome, rather than the action itself.